EASY WAYS TO TEACH VOCABULARY TO YOUNG CHILDREN - Orzikulova Mavsuma Mamatqulovna; Nurmamatova Dilroʻz Pulatjon qizi (International Journal of Literature and Language Studies, 2026)
This article examines effective and accessible strategies for teaching vocabulary to young children, focusing on methods that can be applied by parents, caregivers, and early childhood educators in everyday settings. Vocabulary acquisition during early childhood lays the foundation for later literacy, academic success, and communication skills. The article discusses practical techniques such as labeling objects, using picture books, songs, role-play, repetition, and interactive questioning. It also highlights the importance of a language-rich environment and consistent adult-child interaction in fostering vocabulary growth. The aim is to provide a clear, evidence-informed overview of simple, low-cost methods that support meaningful language development in children aged two to six.